2008
DOI: 10.1017/s0022112008002668
|View full text |Cite
|
Sign up to set email alerts
|

Vortex flow and cavitation in diesel injector nozzles

Abstract: This is the unspecified version of the paper.This version of the publication may differ from the final published version. Permanent repository link:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
97
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(107 citation statements)
references
References 38 publications
7
97
0
3
Order By: Relevance
“…This interaction is similar to vorticity bridging that was observed during the merging of two corotating wing-tip vortices presented by Chang et al 9 and suggests the transport of cavitation vapor between holes. This observation is also in keeping with the previous findings 5,7,8 that observed significant holeto-hole interaction in their larger scale experimental studies.…”
Section: Phys Fluids 22 031703 ͑2010͒supporting
confidence: 93%
See 1 more Smart Citation
“…This interaction is similar to vorticity bridging that was observed during the merging of two corotating wing-tip vortices presented by Chang et al 9 and suggests the transport of cavitation vapor between holes. This observation is also in keeping with the previous findings 5,7,8 that observed significant holeto-hole interaction in their larger scale experimental studies.…”
Section: Phys Fluids 22 031703 ͑2010͒supporting
confidence: 93%
“…Appearing similar to vortex cavitation, as observed in propeller flows, 6 the presence of "cavitation strings" in injector flows has not been widely documented. Gavaises and Andriotis 7 and Andriotis et al, 8 however, showed that the dynamic nature of the nozzle-hole cavitation and sac-vortex interaction leads to hole-to-hole variations in hole flow and spray angle that were attributed to the presence of vortices in the hole entrance region. Although it remains important to quantify the potential influence of these near-hole vortices on the downstream nozzle flow, it is essential to consider the mechanisms of their formation if they are to be controlled and their influence is to be exploited.…”
mentioning
confidence: 99%
“…In [5] there is evidence that geometric-induced and vortex cavitation are interrelated. String cavitation is dramatically enhanced and owes its existence to sources of vapour already present inside the nozzle volume [8]. Moreover, [24] showed that the structure of a vortex core is significantly affected by entrained vapour bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…The former is the most common form of cavitation in such flow orifices and it has become gradually a relatively well-understood phenomenon; appropriate design of the inlet hole curvature and non-cylindrical injection hole shapes (often referred to as tapered) alter cavitation inception, as shown in [6,7]. On the other hand, vortex cavitation is believed to represent a flow feature that depends mainly on the development of turbulent flow within the nozzle rather than a phenomenon that can be controlled by the nozzle design, as it is the case with the geometric-induced cavitation [see 8,9]. Vortex cavitation is commonly found in propellers, hydraulic turbines and hydrofoils as explained in [10,11,12,13]; further studies have also confirmed similar structures in a variety of nozzle designs [14,15] and even at pressures as high as 2000 bar, as shown in [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances dictate the use of extra high injection pressures, of the order of 3000 bar and tiny flow passages (injection holes) of the order of 100-250 μm in diameter, for improved fuel atomisation and combustion efficiency. Under these circumstances, cavitation has been found to develop inside fuel injection nozzles at the early studies of Badock et al (1999), Bergwerk (1959), Chaves et al (1995) and Nurick (1976), followed by Arcoumanis et al (2000), Blessing et al (2003), Mitroglou et al (2014) and Roth et al (2002) in more realistic real-size nozzle geometries offering optical access; equally helpful studies performed in transparent enlarged nozzle replicas [selectively (Andriotis et al 2008;Arcoumanis et al 2000;Miranda et al 2003; Mitroglou and Gavaises 2013;Powell et al 2000)] also indicate that cavitation plays an increasingly significant role in the nozzle's internal flow structure and development. Cavitation inside an injection hole is believed to enhance spray atomisation, either directly through the implosion of cavitation bubbles or indirectly because it increases turbulence in the nozzle flow (Badock et al 1999;Walther 2002); unfortunately, under certain circumstances induces erosion (Dular and Petkovšek 2015;Koukouvinis et al 2016) that may lead to catastrophic failures.…”
mentioning
confidence: 99%